Stromal cell markers are differentially expressed in the synovial tissue of patients with early arthritis. - Ivy Y Choi; Olga N Karpus; Jason D Turner; Debbie Hardie; Jennifer L Marshall; Maria J H de Hair; Karen I Maijer; Paul P Tak; Karim Raza; Jörg Hamann; Christopher D Buckley; Danielle M Gerlag; et al. (PLoS ONE)
Introduction Previous studies have shown increased expression of stromal markers in synovial tissue (ST) of patients with established rheumatoid arthritis (RA). Here, ST expression of stromal markers in early arthritis in relationship to diagnosis and prognostic outcome was studied. Methods ST from 56 patients included in two different early arthritis cohorts and 7 non-inflammatory controls was analysed using immunofluorescence to detect stromal markers CD55, CD248, fibroblast activation protein (FAP) and podoplanin. Diagnostic classification (gout, psoriatic arthritis, unclassified arthritis (UA), parvovirus associated arthritis, reactive arthritis and RA), disease outcome (resolving vs persistent) and clinical variables were determined at baseline and after follow-up, and related to the expression of stromal markers. Results We observed expression of all stromal markers in ST of early arthritis patients, independent of diagnosis or prognostic outcome. Synovial expression of FAP was significantly higher in patients developing early RA compared to other diagnostic groups and non-inflammatory controls. In RA FAP protein was expressed in both lining and sublining layers. Podoplanin expression was higher in all early inflammatory arthritis patients than controls, but did not differentiate diagnostic outcomes. Stromal marker expression was not associated with prognostic outcomes of disease persistence or resolution. There was no association with clinical or sonographic variables. Conclusions Stromal cell markers CD55, CD248, FAP and podoplanin are expressed in ST in the earliest stage of arthritis. Baseline expression of FAP is higher in early synovitis patients who fulfil classification criteria for RA over time. These results suggest that significant fibroblast activation occurs in RA in the early window of disease.